SOLUTIONS OF A TWO-COMPONENT GINZBURG-LANDAU SYSTEM - GAO, QI (My University, 2013)
We study Ginzburg–Landau equations for a complex vector order parameter to a two-component system. We discuss the existence, uniqueness, asymptotics, monotonicity and stability of solutions by extending Alama-Bronsard-Mironescu's results in a more general case.
Keywords: Calculus of variations; Elliptic equations and systems; Superconductivity; Vortices; Mathematics; Mathematics